Synthesis of Novel Benzo[6,7][1,4]oxazepino[4,5-a]quinazolinone Derivatives via Transition-Metal-Free Intramolecular Hydroamination - Mahdavi, Mohammad; Foroughi, Niloufar; Saeedi, Mina; Karimi, Maryam; Alinezhad, Heshmatollah; Foroumadi, Alireza; Shafiee, Abbas; Akbarzadeh, Tahmineh (Synlett, 2014)
Novel benzo[6,7][1,4]oxazepino[4,5-a]quinazolinone derivatives were synthesized through an efficient 7-exo-dig hydroamination of 3-substituted-2-[2-(prop-2-yn-1-yloxy)phenyl]-2,3-dihydroquinazolin-4(1H)-ones in the presence of potassium tert-butoxide (KOt-Bu) in DMF at 130 °C.
Keywords: hydroamination; 2-aminobenzamides; terminal alkynes; 7-exo-dig; N-heterocycles